1973
DOI: 10.1071/bi9731095
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Two Ecotypes of Phytophthora Drechsleri Tucker Occurring in Australian Native Forests

Abstract: A total of 70 isolates of P. drechsleri from Australian native eucalypt forests were separated into two distinct ecotypes. The "northern" ecotype occurred from North Queensland to the south of New South Wales, while the "southern" ecotype occurred in South Australia, Victoria, Tasmania, and New South Wales.The northern ecotype on average grew faster on a variety of media than did the southern one, but ecotypes could not be recognized unequivocally on this basis. The upper temperature limit for growth of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Moreover, the high-temperature criterion did not always correlate with the other identifying features (Klisiewicz & Beard 1976;Banihashemi & Ghaisi 1993) and as a result, some isolates were described as intermediate between both species (Flowers et al 1973;Shepherd & Pratt 1973;Klisiewicz 1977;Stanghellini & Kronland 1982). This led some investigators to cast doubt upon the validity of temperature response as the main distinguishing feature (Shepherd & Pratt 1973;Klisiewicz 1977), while others simply rejected P. drechsleri as an acceptable species (Bumbieris 1974;Gerrettson-Cornell 1979). Some maintained that P. drechsleri should be kept as an acceptable species until more conclusive data were obtained (Kannaiyan et al 1980;Krö ber 1981).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the high-temperature criterion did not always correlate with the other identifying features (Klisiewicz & Beard 1976;Banihashemi & Ghaisi 1993) and as a result, some isolates were described as intermediate between both species (Flowers et al 1973;Shepherd & Pratt 1973;Klisiewicz 1977;Stanghellini & Kronland 1982). This led some investigators to cast doubt upon the validity of temperature response as the main distinguishing feature (Shepherd & Pratt 1973;Klisiewicz 1977), while others simply rejected P. drechsleri as an acceptable species (Bumbieris 1974;Gerrettson-Cornell 1979). Some maintained that P. drechsleri should be kept as an acceptable species until more conclusive data were obtained (Kannaiyan et al 1980;Krö ber 1981).…”
Section: Introductionmentioning
confidence: 90%
“…However, it is apparent that ecological specialization towards response to Trichoderma and other agencies could lead to speciation and other complex phylogenetic relationships in the heterothallic species. Such a phenomenon might account for the occurrence of two ecotypes among isolates of Phytophthora drechsleri from Eucalypt forests in Australia, one A2 and responsive to Trichoderma, the other sterile and nonresponsive (Shepherd and Pratt, 1973). …”
Section: Ecological and Phylogenetical Implicationsmentioning
confidence: 99%
“…The results (Table 3) are similar to those reported by other authors (Tucker 1931;Leonian 1934;Schwinn 1959;Waterhouse 1963) for isolates from other countries. Shepherd and Pratt (1973) have reported that cultures of P. drechsleri Tucker were incapable of growth at 44°C, but when such cultures were returned to 25°C growth would sometimes recommence after a lag period. The tolerance to high temperature of the Queensland isolate of P. nicotianae var.…”
Section: (B) Growth Experimentsmentioning
confidence: 99%
“…Effects of temperature, presence or absence of sterol, and form of nitrogen source on mycelial growth rates were determined according to Shepherd and Pratt (1973). Electronically controlled incubators were used to maintain desired incubation temperatures to ±0'1 DC.…”
Section: (C) Growth Testsmentioning
confidence: 99%
See 1 more Smart Citation